Res publica. Étude et réception d’une constellation - Virginie Hollard; Romain Meltz (Astérion)
Based on Claudia Moatti’s Res publica. Histoire romaine de la chose publique, we strive to draw the outlines of what would be a historical science of antiquity that would isolate, in order to protect itself, the political representations that link us to Rome? The aim here is to study the political concepts used in ancient Rome by placing, at the fore, language and anthropology of the practices that we are trying to identify, in the background. This feature therefore seeks to extend Claudia Moatti’s work by resuming the study of Res publica to perceive how it has been received by posterity.